Decarbonizing the Indian Dream: A Localized Framework for Sustainable Growth in the Building Sector - Kanda, Vijay (Digital Repository of Theses, 2024)
The building sector is a significant source of greenhouse gas emissions and is critical to achieving Net Zero by 2070 in India. This thesis proposes a strategic plan for decarbonizing energy and water efficiency in the building sector. The plan consists of a framework that integrates various technological, financial, and social aspects of the transition, such as renewable energy, building envelope optimization, intelligent water management, green roofs, rainwater harvesting, green bonds, performance contracts, and user perceptions. The thesis uses Quantitative methods to assess the framework's feasibility, effectiveness, and acceptability based on data collected from surveys, interviews, and case studies. The thesis provides actionable insights for corporate management, businesses, building professionals, and policymakers and aims to be the first comprehensive blueprint for India's building sector decarbonization. The thesis demonstrates that the framework can reduce building sector emissions by 30%, and save 40% of energy and 50% of water consumption, contributing to sustainable growth and Net Zero achievement.